The Effects of a Nurse-Led Education and Counseling Program on Dyspnea, Health Status, and Care Dependency in Patients With Chronic Obstructive Pulmonary Disease: A Feasibility Study. Issue 4 (November 2019) - Helvaci, Aylin; Gok Metin, Zehra; Ozdemir, Leyla; Ergun, Pinar
The aim of this feasibility study was to determine the effects of a nurse-led education and counseling program for chronic obstructive pulmonary disease (COPD-ECP) on dyspnea, health status, and care dependency in patients. A quasi-experimental, pre-posttest research design without a control group was performed on 30 COPD patients. The patients received an 8-week COPD-ECP via home visits during the first 4 weeks and via phone interviews in the subsequent 4 weeks. After completion of COPD-ECP and a 4-week break, a final follow-up was conducted at the end of 12th week. The Dyspnea-12, COPD Assessment Test (CAT), and Care Dependency Scale (CDS) scores were calculated during the first interview, and on the 4th, 8th, and 12th week of the study. The patients completed all sessions of COPD-ECP without side effects. There was a significant decrease in the total Dyspnea-12 scores at the end of the study period. Compared to the baseline assessment, CAT total scores significantly decreased in the 4th, 8th, and 12th week ( p < 0.05), and CDS scores showed a significant reduction at the 12th week ( p < 0.05). In conclusion, COPD-ECP is feasible in regular clinical practice and well accepted by patients, and it seems to improve health status and decrease dyspnea, and care dependency. Future randomized controlled studies are warranted to explore the effects of COPD-ECP on fatigue, cough and sleep problems, and the best innovative strategies to improve the efficiency of COPD-ECP.